Optimization of Business Plan in Creating the Creativity of Home Business Actors in Aisyiyah Members - Nur Isna Inayati; Kurnia Ritma Dhanti; Ira Hapsari (Universitas Muhammadiyah Purwokerto, 2023)
The Indonesian nation, including Muslim women's movements such as Aisyiyah, is faced with the challenges of very complex problems and dynamics of social change. For example, the problem of poverty, and violence against women and children. There are several obstacles for women in increasing their business, including not understanding the business plan in doing business. As we know today technology continues to develop and telecommunications are increasingly innovating. With advances in the field of information and communication technology today, the world no longer knows boundaries, distance, space and time. The internet has had a great impact because it created a new paradigm in entrepreneurship and business. Community Service Activities the Science and Technology Program for the Community with the title